The cytotoxic effect of Cananga odorata (CO) essential oil on skin cancer is not via TP53 gene expression modulation - Anuar, Muhammad Ashraf Fithri (2023)
Introduction: Skin cancer is one of the most common cancers worldwide. Cananga odorata (CO) essential oil (EO) has been reported to have anticancer and antioxidant properties. Hence, it may have the potential to be used as a topical treatment for skin cancer. The aim of this study is to assess the cytotoxic effect of CO EO on skin cancer, the pro-apoptotic TP53 gene expression, and its protein (p53) secretion. Materials and Methods: A431 squamous skin cancer cells and HFF1 fibroblast cells were treated with CO EO at 125, 250, and 500 μg/ml for 24 h. Their morphology was observed at 20-40x magnification. TP53 gene expression in these cells was examined by real-time PCR. p53 protein secretion in the conditioned media was assessed using western blot. Results: CO EO treated A431 cells exhibited loss of cellular margin and higher non-viable cells at all concentrations. Meanwhile, HFF1 cells treated with 125 μg/ml CO EO showed no significant changes. At 250 and 500 μg/ml, there was no significant changes in TP53 gene expression in A431 cells, but higher p53 protein secretion was observed. Conclusion: Our findings suggest that CO EO was cytotoxic to skin cancer at 250 and 500 μg/ml without augmenting TP53 gene expression. Hence, further investigations into CO EO effect on other apoptotic or anti-proliferative regulatory genes are required to establish its underlying molecular mechanism leading to its cytotoxic effect in skin cancer.